Extensive ITR expansion of the 2022 Mpox virus genome through gene duplication and gene loss - Brinkmann, Annika; Kohl, Claudia; Pape, Katharina; Bourquain, Daniel; Thürmer, Andrea; Michel, Janine; Schaade, Lars; Nitsche, Andreas (Virus genes, 2023)
Poxviruses are known to evolve slower than RNA viruses with only 1–2 mutations/genome/year. Rather than single mutations, rearrangements such as gene gain and loss, which have been discussed as a possible driver for host adaption, were described in poxviruses. In 2022 and 2023 the world is being challenged by the largest global outbreak so far of Mpox virus, and the virus seems to have established itself in the human community for an extended period of time. Here, we report five Mpox virus genomes from Germany with extensive gene duplication and loss, leading to the expansion of the ITR regions from 6400 to up to 24,600 bp. We describe duplications of up to 18,200 bp to the opposed genome end, and deletions at the site of insertion of up to 16,900 bp. Deletions and duplications of genes with functions of supposed immune modulation, virulence and host adaption as B19R, B21R, B22R and D10L are described. In summary, we highlight the need for monitoring rearrangements of the Mpox virus genome rather than for monitoring single mutations only.